2010
DOI: 10.1051/0004-6361/200810366
|View full text |Cite
|
Sign up to set email alerts
|

Fine-structure infrared lines from the Cassiopeia A knots

Abstract: Aims. Archival observations of infrared fine-structure lines of the young Galactic supernova remnant Cassiopeia A allow us to test existing models and determine the physical parameters of various regions of the fast-moving knots, which are metal-dominated clouds of material ejected by the supernova explosion. Spitzer data are used to determine the fluxes of the O, Ne, Si, S, Ar, and Fe ion fine-structure lines originating in the fast-moving knots. The ratios of these line fluxes are used as plasma diagnostics.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 58 publications
(158 reference statements)
9
73
0
Order By: Relevance
“…Because the gas in Cas A can be ionised due to shocks and/or the radiation field, we assume that most of the [Si ii] emission comes from the ionised gas phase. The latter assumption is supported by the absence of any detected [O i] 63 µm or 145 µm line emission from Cas A (Docenko & Sunyaev 2010;. With a critical density of 10 3 cm −3…”
Section: Appendix B: Line Emissionmentioning
confidence: 84%
See 1 more Smart Citation
“…Because the gas in Cas A can be ionised due to shocks and/or the radiation field, we assume that most of the [Si ii] emission comes from the ionised gas phase. The latter assumption is supported by the absence of any detected [O i] 63 µm or 145 µm line emission from Cas A (Docenko & Sunyaev 2010;. With a critical density of 10 3 cm −3…”
Section: Appendix B: Line Emissionmentioning
confidence: 84%
“…With unrealistically high dust masses needed to reproduce the IR-submm dust SED, we can exclude Mg0.7SiO2.7, CaAl12O19 and Al2O3 grains as the dominant dust species in Cas A. Also amorphous carbon grains might not be a plausible major dust component in Cas A due to the overwhelmingly oxygen-rich composition of the remnant (Chevalier & Kirshner 1979;Docenko & Sunyaev 2010). Due to the presence of a variety of metals in different parts of the SN ejecta (e.g., Rho et al 2008;Arendt et al 2014), the condensation of SN dust with a range of different dust compositions throughout the remnant might be more realistic 22 .…”
Section: Dust Sed Modelling and Resultsmentioning
confidence: 99%
“…In a dense knot, the reverse shock is attenuated due to energy conservation. Following Docenko & Sunyaev (2010), a 2000 km s −1 reverse shock will be slowed to 200 km s −1 when crossing a knot 100 times denser than the interclump medium. For a 200 km s −1 shock, the gas temperature at the shock front reaches some 10 7 K, and pre-existing molecules, including CO, will be destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…The physical structure of shocked SN ejecta has been discussed in several previous studies (41)(42)(43)(44)(45)(46). A noticeable characteristic of the shocks propagating into SN ejecta composed of calculation is done by using a shock code developed for SN ejecta (45,47,48) with updated atomic constants for phosphorus.…”
Section: [P Ii] and [Fe Ii] Emission From Shocked Sn Ejectamentioning
confidence: 99%
“…In principle, there could be some emission from the preshock region photoionized by the shock radiation (43,44,46), but in the Cas A knots the observed high electron densities (3 × 10 3 -2 × 10 In SN ejecta swept-up by a reverse shock, it is likely that a wide range of preshock densities and also a wide range of shock speeds are present (44,45). We ran a grid of models and have found that, in order to match the observed [Fe II] line ratios, the shock speed should be < ∼ 50 km s −1 and the preshock densities should be > ∼ 100 cm −3 .…”
Section: [P Ii] and [Fe Ii] Emission From Shocked Sn Ejectamentioning
confidence: 99%